Reviewer Acknowledgements and Introduction of New Numbering Format: Special Edition from the Cirebon International Health Symposium - GHMJ (Global Health Management Journal), Volume 8, Number 1s, 2025 - GHMJ (Global Health Management Journal) (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Starting from this edition, GHMJ (Global Health Management Journal) designates Special Editions with an “s” in the numbering (e.g., Vol. 8, No. 1s) to indicate their inclusion as a section within the ongoing issue, with all articles undergoing rigorous double-blind peer review to uphold the journal’s commitment to academic excellence. This issue of the Global Health Management Journal (Vol. 8, No. 1s, 2025) presents a diverse selection of articles reflecting the depth and breadth of current health research. From applied sciences, two studies examine the antimicrobial potential of mango peel extracts in inhibiting Staphylococcus aureus and Escherichia coli (‘Adawiyah et al., 2025; Siskanti et al., 2025), highlighting the value of natural resources in public health innovation. In the field of epidemiology and public health, important clinical insights are offered through studies on the relationship between antiretroviral therapy duration and kidney function in HIV/AIDS patients, as well as a retrospective review of psoriasis cases in Cirebon (Ayudhipasha et al., 2025; Putra et al., 2025). Medical education is addressed through an exploration of students' perceptions of ideal lecturer qualities in problem-based learning environments (Erlangga et al., 2025). Meanwhile, research in medical technology includes analyses of gene polymorphisms related to tuberculosis and diabetes, along with clinical evaluations of corneal curvature changes following cataract surgery (Oktaviyati et al., 2025; Putri et al., 2025; Nuruzzahrah et al., 2025). Finally, a study on mental health investigates the factors influencing the quality of life among patients with type 2 diabetes (Hidayat et al., 2025), emphasizing the ongoing need to consider psychosocial dimensions in chronic disease management. Together, these articles contribute to a growing body of evidence that supports more holistic and innovative approaches to global and community health. Link to download: https://publications.inschool.id/index.php/ghmj/issue/view/CIHES01s We extend our heartfelt appreciation to the reviewers who have played a crucial role in refining and enhancing these works. Editor-in-chief Prof. Andrew John Macnab Managing Editors Doni Marisi Sinaga, M.Sc. Kukuh Madyaningrana, M.Biotech. Ph.D. Journal Managers Suyitno, M.PHM Maretalinia, M.A Internal Reviewers from Faculty of Medicine, Universitas Swadaya Gunung Jati, Indonesia Donny Nauphar, M.Si.Med Ahmad Fariz Malvi Zamzam Zein, Sp.PD, FINASIM, MM, FACP Bambang Wibisono, MH Tiar M. Pratamawati, MM, M.Biomed Tissa Octavira Permatasari, M.MedEd Witri Pratiwi, M.Kes. Vivi Meidianawaty, M.MedEd External Reviewers Supim Wongtongtair, Ph.D. (Srinakharinwirot University, Thailand) Eligible reviewers may be considered for future roles on our Editorial Board, and receive Exclusive Publishing Opportunity and the chance to publish Guest Editorial Papers at no cost. Simply register on our website and select the